Reformulation of The Regulations Regarding Changes In The Status of Individual Companies To Capital Partnership Companies With Legal Certainty - Natasha Graciela Hastika; Djumikasih; Fathul Laila (Faculty of Law, Merdeka University Surabaya, Indonesia, 2025)
Indonesia's national economic recovery requires increased competitiveness of business actors, including through the development of regulations for establishing business entities. The Job Creation Law and Government Regulation No. 8 of 2021 introduced the concept of an Individual Limited Liability Company (PT) which allows the establishment of a PT by one person without a notarial deed, for micro and small business actors. However, the change in status of an Individual PT to a capital partnership PT must be carried out with a notarial deed, which creates legal uncertainty and challenges in implementing the regulation. In addition, the lack of socialization and education regarding the regulation of Individual PTs has resulted in low understanding among business actors. This study uses a normative legal method with a statutory, conceptual, and historical approach, as well as an analysis of grammatical and systematic interpretation of primary, secondary, and tertiary legal materials. Through interviews with notaries, this study examines the legal consequences of the deed of change of status of an Individual PT and provides recommendations to clarify future legal norms in changing the status of an individual company to a capital partnership. It is hoped that the research results can support the implementation of more effective individual PT regulations, provide legal certainty for business actors, and strengthen the contribution of MSMEs to national economic growth